Response to Pegylated Interferon Plus Ribavirin in Patients with Hepatitis C Virus Genotype 6a Infection from Guangdong and Guangxi Province of China - Wangxia Tong; Jianyun Zhu; Ning Luo; Xiaohua Yang; Zhiying Lei; Xiaoliang Huang; Zhixin Zhao; Xiaohong Zhang; Zhiliang Gao; Zhonghua Jiang (Gastroenterology Research and Practice)
Aim. Our aim is to survey the treatment effect of PEG-IFN plus ribavirin in patients infected with HCV genotype 6a in Guangdong and Guangxi province of China and investigate best course of antiviral treatment for patients with HCV-6a infection. Methods. 515 eligible patients received subcutaneous 180 μg PEG-IFNα-2a or 1.5 μg/kg PEG-IFNα-2b once weekly plus oral ribavirin. Primary outcome was SVR by intention-to-treat analysis. Secondary outcome was RVR, cEVR, ETR, and relapse rate. Results. SVR in patients with HCV-6a infection treated for 48 weeks was comparable to that in patients with HCV-2/3 infection (80.9% versus 82.5%, p=0.812) and higher than that in patients with HCV-1b infection (80.9% versus 67.2%, p=0.014). ETR (98.9% versus 90.6%, p=0.016), virological response at month 3 of end-of- treatment (88.8% versus 76.6%, p=0.044), SVR (80.9% versus 65.6%, p=0.032), and virological response at month 12 of end-of-treatment (76.4% versus 60.9%, p=0.04) in patients with HCV-6a infection treated for 48 weeks were higher than those in patients with HCV-6a infection treated for 24 weeks. Conclusion. SVR in patients with HCV-6a treated for 48 weeks was comparable to that in patients with HCV-2/3 infection and higher than that in patients with HCV-1b infection; patients with HCV-6a infection treated for 48 weeks had a superior treatment response than patients treated for 24 weeks.